A multinational study of neurological performance in antiretroviral therapy-naïve HIV-1-infected persons in diverse resource-constrained settings - Robertson K. (2017)
Little is known about how the prevalence and incidence of neurological disease in HIV-infected patients in resource-limited settings. We present an analysis of neurological and neurocognitive function in antiretroviral naïve individuals in multinational resource-limited settings. This prospective multinational cohort study, a substudy of a large international randomized antiretroviral treatment trial, was conducted in seven low-and middle-income countries in sub-Saharan Africa, South America, and Asia. Subjects were HIV-infected and met regional criteria to initiate antiretroviral therapy. Standardized neurological examination and a brief motor-based neuropsychological examination were administered. A total of 860 subjects were studied. Overall 249 (29%) had one or more abnormalities on neurological examinations, but there was a low prevalence of HIV-associated dementia (HAD) and minor neurocognitive disorder (MND). Twenty percent of subjects had evidence of peripheral neuropathy. There were significant differences across countries (p < 0.001) in neuropsychological test performance. In this first multinational study of neurological function in antiretroviral naïve individuals in resource-limited settings, there was a substantial prevalence of peripheral neuropathy and low prevalence of dementia and other CNS diseases. There was significant variation in neurocognitive test performance and neurological examination findings across countries. These may reflect cultural differences, differences in HIV-related and unrelated diseases, and variations in test administration across sites. Longitudinal follow-up after antiretroviral treatment initiation may help to define more broadly the role of HIV in these differences as well as the impact of treatment on performance. © Journal of NeuroVirology, Inc. 2011.